Youth and educated unemployment in North East India - Marchang, Reimeingam (IASSI Quarterly: Contributions of Indian Social Science)
Youth and educated unemployment problems continue as the population rapidly grows and education develops while job opportunities are limited due to economic underdevelopment. Unemployment problems of educated and youth are more severe in most of the NE states than in the country. The youth unemployment problem was more severe in urban than rural areas and for females than males in most of the NE states as in the country. The prevalence of educated unemployment is, both rural and urban phenomena, however, it is more severe for females than males in most of the NE states.- Reproduced
Keywords: Unemployment, Youth educated, North East India